Strategi dan Efektivitas Pertumbuhan Jumlah Event di Kabupaten Banyuwangi Periode Tahun 2013-2020 - Diena Mutiara Lemy; Ali (CV. Creative Tugu Pena, 2024)
In the period 2010-2020, there was an exponential increase in the number of Tourism events in Banyuwangi Regency. The increasing number of events is interesting on a provincial, as well as national scale because no other district/municipality has an equivalent increase. This article will focus on how the district government's efforts to drive this increase and how the impact of the significantly increased number of events on the condition of Banyuwangi Regency Tourism. This research uses qualitative methods that also pay attention to quantitative data to analyze how event development policies in Banyuwangi have an effect on Banyuwangi Regency and its people in 2010-2020. The